New multituberculate mammals from the mid-Cretaceous (lower Cenomanian) Wayan Formation of southeastern Idaho and implications for the early evolution of Cimolodonta. Issue 2 (4th March 2019) - Weaver, Lucas N.; Wilson, Gregory P.; Krumenacker, L. J.; Mclaughlin, Kayla; Moore, Jason R.; Varricchio, David J.
ABSTRACT: During the mid-Cretaceous, multituberculate mammal communities were restructured, as 'plagiaulacidan' multituberculates, common from the Middle Jurassic through Early Cretaceous, began to be replaced by the Cimolodonta, a clade that would come to be the most abundant and diverse group of mammals during the Late Cretaceous and early Paleocene. Although these broad strokes of multituberculate evolutionary history are well documented, the only fossil assemblage detailing this rise of the Cimolodonta during the Early–Late Cretaceous transition comes from the Mussentuchit Member of the Cedar Mountain Formation in central Utah. Here, we report on nine new multituberculate specimens from the Wayan Formation of southeastern Idaho, representing the second and northernmost record of multituberculate mammals from near the Early–Late Cretaceous boundary of North America. The Wayan assemblage consists of isolated cimolodontan premolars and molars representing at least four taxa, including one new species, Cimolodon akersteni . The presence of Cimolodon in the Wayan assemblage represents the earliest occurrence of this genus and the first appearance of a clade nested within Cimolodonta (the Cimolodontidae). Only two species are shared between the Wayan Formation and the Mussentuchit Member, cf. Paracimexomys perplexus and Bryceomys intermedius . All other specimens differ morphologically from any known mid-Cretaceous multituberculate species. The differences in the Wayan and Mussentuchit multituberculate local faunas could be due to differences in age, biogeography, paleoenvironment, sampling bias, or some combination of these factors. These new specimens reveal a greater diversity of mid-Cretaceous multituberculates than was previously recognized and provide new insights into the early evolution of Cimolodonta.